TOPONIMI OBJEK WISATA DI KECAMATAN LOHIA KABUPATEN MUNA (PENDEKATAN ETNOLINGUISTIK) - Sukmawati; La Ino; Ali Mustopa (Program Studi Sastra Indonesia Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
The problem in this study is how the toponymy of tourist objects in Lohia District, Muna Regency. The purpose of this research is to describe the toponymy of tourist objects in Lohia District, Muna Regency. This research is a qualitative descriptive research. The data in this study are in the form of toponymy of tourist objects and the background of naming tourist objects in Lohia District, Muna Regency. The source of data in this study is derived from utterances given by traditional leaders in Lohia District, Muna Regency. The techniques in data collection are using interview techniques, note-taking techniques, and recording techniques. The result of this research is that the names of tourist attractions in Lohia District, Muna Regency, are motivated by three aspects of naming, namely 1) aspects of embodiment which include water settings, (floating caves, Meleura beach, Motonuno lake), earth surface settings or earth forms (Bumburu lake, Kantinu), natural environment settings (Bumburu lake), 2) aspects of community/community habits (Napabale beach), 3) cultural aspects (Mondawuhano Ndoke lake). Keywords: Toponymy; Naming of Tourism Objects; Lohia Sub-district